2021
DOI: 10.3389/fnsys.2021.749444
|View full text |Cite
|
Sign up to set email alerts
|

Chewing and Cognitive Improvement: The Side Matters

Abstract: Chewing improves cognitive performance, which is impaired in subjects showing an asymmetry in electromyographic (EMG) masseter activity during clenching. In these subjects, the simultaneous presence of an asymmetry in pupil size (anisocoria) at rest indicates an imbalance in Ascending Reticular Activating System (ARAS) influencing arousal and pupil size. The aim of the present study was to verify whether a trigeminal EMG asymmetry may bias the stimulating effect of chewing on cognition. Cognitive performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…Although the projections of sensory afferents from the mesencephalic trigeminal sensory nucleus (Me5) [ 113 , 114 ] and the nucleus of tractus solitarius (NTS) [ 115 ] to the LC exert influences on cognitive functions [ 116 ], an important regulatory component on the core noradrenergic neurons in the LC include the peri-LC afferent innervations. Noradrenergic LC neurons possess long dendrites that pass through the surrounding small nuclei-like regions around the LC, which receive separate inputs from a variety of brain regions, including the prefrontal and infralimbic cortex, the amygdala, and the dorsal raphe nucleus [ 117 ].…”
Section: Anatomical Overviewmentioning
confidence: 99%
“…Although the projections of sensory afferents from the mesencephalic trigeminal sensory nucleus (Me5) [ 113 , 114 ] and the nucleus of tractus solitarius (NTS) [ 115 ] to the LC exert influences on cognitive functions [ 116 ], an important regulatory component on the core noradrenergic neurons in the LC include the peri-LC afferent innervations. Noradrenergic LC neurons possess long dendrites that pass through the surrounding small nuclei-like regions around the LC, which receive separate inputs from a variety of brain regions, including the prefrontal and infralimbic cortex, the amygdala, and the dorsal raphe nucleus [ 117 ].…”
Section: Anatomical Overviewmentioning
confidence: 99%
“…Another limitation was selecting chewing gum for the placebo group. Several studies demonstrated the effects of chewing on cognitive improvement 35,36 . The positive effect of chewing gum on cognition in both groups may influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal sensory in recent years has been shown to be associated with the functioning and dysfunction of the central nervous system, and it has been suggested that its alteration may play a role in the genesis or, at least, in the worsening of chronic neurodegenerative disorders [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probably this action is partly related to the relationship between the trigeminal and arousal systems and, in particular, to the activity of the locus coeruleus [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%